A trajectory piecewise-linear approach to model order reduction and fast simulation of nonlinear circuits and micromachined devices. - Rewienski, M.
In this paper, we present an approach to nonlinear model reduction based on representing a nonlinear system with a piecewise-linear system and then reducing each of the pieces with a Krylov projection. However, rather than approximating the individual components as piecewise linear and then composing hundreds of components to make a system with exponentially many different linear regions, we instead generate a small set of linearizations about the state trajectory which is the response to a "training input." Computational results and performance data are presented for an example of a micromachined switch and selected nonlinear circuits. These examples demonstrate that the macromodels obtained with the proposed reduction algorithm are significantly more accurate than models obtained with linear or recently developed quadratic reduction techniques. Also, we propose a procedure for a posteriori estimation of the simulation error, which may be used to determine the accuracy of the extracted trajectory piecewise-linear reduced-order models. Finally, it is shown that the proposed model order reduction technique is computationally inexpensive, and that the models can be constructed "on the fly," to accelerate simulation of the system response.
Keywords: Krylov projection; MEMS; PWL system; Fast simulation; Macromodels; Microelectromechanical systems; Micromachined devices; Micromachined switch; Model order reduction; Nonlinear analog circuits; Nonlinear circuits; Nonlinear dynamical systems; Nonlinear model reduction; Nonlinear system representation; Piecewise-linear system; State trajectory; Trajectory piecewise-linear approach